Motor imagery for paediatric neurorehabilitation: how much do we know? Perspectives from a systematic review - Gentile, Amalia Egle; Rinella, Sergio; Desogus, Eleonora; Verrelli, Cristiano Maria; Iosa, Marco; Perciavalle, Vincenzo; Ruggieri, Martino; Polizzi, Agata (Frontiers in Human Neuroscience, 2024)
Background: Motor Imagery (MI) is a cognitive process consisting in mental simulation of body movements without executing physical actions: its clinical use has been investigated prevalently in adults with neurological disorders. Objectives: review of the best-available evidence on the use and efficacy of MI interventions for neurorehabilitation purposes in common and rare childhood neurological disorders. Methods: systematic literature search conducted according to PRISMA by using the Scopus, PsycArticles, Cinahl, PUBMED, Web of Science (Clarivate), EMBASE, PsychINFO, and COCHRANE databases, with levels of evidence scored by OCEBM and PEDro Scales. Results: 22 original studies were retrieved and included for the analysis; MI was the unique or complementary rehabilitative treatment in 476 individuals [aged 5 to 18 years] with 10 different neurological conditions including, cerebral palsies, stroke, coordination disorders, intellectual disabilities, brain and/or spinal cord injuries, autism, pain syndromes, and hyperactivity. The sample size ranged from single case reports to cohorts and control groups. Treatment lasted 2 days to 6 months with 1 to 24 sessions. MI tasks were conventional, graded or ad-hoc. MI measurement tools included movement assessment batteries, mental chronometry tests, scales, and questionnaires, EEG, and EMG. Overall, the use of MI was stated as effective in 19/22, and uncertain in the remnant studies. Conclusions: MI could be a reliable supportive/add-on (home-based) rehabilitative tool for pediatric neurorehabilitation; its clinical use, in children, is highly dependent on the complexity of MI mechanisms, which are related to the underlying neurodevelopmental disorder.